Distribution of Organic Matter and Nutrient Content in a Eucalyptus Hybrid Plantation on Lateritic Soil in West Bengal - Gupta, A. C.; Raturi, D. P. (Indian Forester, 1984)
Distribution of organic matter and plant nutrients in a 10 yearS old Eucalyptus hybrid plantation raised on lateritic soil in Mauza Barihote, Hoomgarh Range, East Midoapore Forest Division, West Bengal have been discussed. It seems that Eucalyptus hybrid is well suited for this tract when growth with adequate manuring. From the growth rate of this species on average type of soil the crop at the end of the first rotation can be expected to yield about 90 tonnes of usable nood per ha which should increase with better inputs and experience in raising these plantations.